The white princess eaudiobook - Gregory, Philippa (Plantagenet and Tudor Novels, 2014)
Crowned the "queen of royal fiction" by USA Today, Philippa Gregory is a #1 New York Times bestselling author and winner of the Romantic Novelists' Association's RoNA Award for The Other Boleyn Girl. The White Princess continues the saga of the War of the Roses as Princess Elizabeth of York weds Henry VII after he kills Richard III in battle. Now queen, Elizabeth must decide where her loyalties lie—with the house she's descended from or the husband she's growing to love.